Laporan Kasus Terapi Kombinasi Kuretase dan Cimetidine Oral pada Pasien Moluskum Kontangiosium - Annisa Fildza Hashfi; Nurrachmat Mulianto; Winda Wijayanti; Niluh Wijayanti (PT Dexa Medica, 2022)
Background: Molluscum contagiosum is an infectious disease of the skin caused by poxvirus. The virus may be transmitted through direct skin and mucous membrane contact, including sexual contact, and through contaminated fomites. The prevalence of sexually transmitted molluscum contagiosum has increased in recent years. This disease causes anxiety and discomfort for the patients. Diagnosis of molluscum contagiosum is made based on history taking, physical examination, dermoscopic examination, and histopathological examination. Proper diagnosis and management can help to reduce risk of recurrence. Case: A 26-year-old woman with main complaint of developing shiny white rashes on her thighs and buttocks since 3 months ago. The nodules felt itchy yet painless. At first, only 4 papules appeared on the buttocks. In the last month, the nodules multiplied and spread to the thighs. The patient had tried to squeeze the nodule and rice-like white mass came out. The patient had history of unprotected sexual intercourse. Dermatological examination on the right and left femoral regions and the gluteus, found that there were discrete, multiple shiny white pearl-like papules of 0.1-0.5 cm in size, smooth surface, well-defined, dome-shaped, umbilicated with caseous plug. Dermoscopic examination showed a white to yellow polylobular appearance with crown vessel. Histopathological examination showed an appearance of intracytoplasmic eosinophil inclusion bodies (molluscum bodies). Discussion: Clinical findings such as discrete multiple, pearl-colored, umbilicated dome-shaped papules, are characteristic features of molluscum contagiosum. Dermoscopic examination results and histopathological images also support the diagnosis of molluscum contagiosum. Treatment was carried out using curettage on the lesions and prescription of oral cimetidine 2x800 mg for 2 months. No recurrence was found after 5 months of follow-up